Integrating three-dimensional printing and bioprinting technologies to develop a stretchable in vitro model of the human airway - Chan, Junned; Rubio, Julian Gonzalez; O'Dwyer Lancaster-Jones, Oscar; Verma, Yashasvi; Büchter, Charlotte; Jockenhoevel, Stefan; De Laporte, Laura; Trilling, Mirko; Thiebes, Anja Lena; Duarte Campos, Daniela Filipa (Bio-design and manufacturing, 2025)
The global demand for in vitro respiratory airway models has surged due to the coronavirus disease 2019 (COVID-19) pandemic. Current state-of-the-art models use polymer membranes to separate epithelial cells from other cell types, creating a nonphysiological barrier. In this study, we applied three-dimensional (3D) printing and bioprinting to develop an in vitro model where endothelial and epithelial cells were in direct contact, mimicking their natural arrangement. This proof-of-concept model includes a culture chamber, with an endothelial bioink printed and perfused through an epithelial channel. In silico simulations of the air velocity within the channel revealed shear stress values ranging from 0.13 to 0.39 Pa, aligning with the desired in vivo shear stress observed in the bronchi regions (0.1-0.4 Pa). Biomechanical movements during resting breathing were mimicked by incorporating a textile mesh positioned away from the cell-cell interface. The epithelial channel demonstrated a capacity for compression and expansion of up to −14.7% and +6.4%, respectively. Microscopic images showed that the epithelial cells formed a uniform monolayer within the lumen of the channel close to the bioprinted endothelial cells. Our novel model offers a valuable tool for future research into respiratory diseases and potential treatments under conditions closely mimicking those in the lung.
Veröffentlicht: 27. Juni 2025
Gesehen am 03.11.2025